2023
DOI: 10.3390/su15054157
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Outdoor Activities and Campus Landscape on University Students’ Subjective Well-Being during the COVID-19 Pandemic

Abstract: COVID-19 is reshaping the relationship between humans and their living environment, potentially generating a profound impact on human physical and mental health and quality of life. The objective of this study was to explore how outdoor activities and the campus landscape impacted the subjective well-being (SWB) of Chinese university students in the pre-COVID-19 era (before December 2019) and during the COVID-19 era (from December 2019 to early December 2022). This study collected 439 valid questionnaires from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…However, the study of Baetens et al (2022) shows the pandemic does adversely affect undergraduates' subjective well-being in college. Chen and Ye (2023) found that compared with the period before the epidemic, undergraduates' subjective well-being in college had decreased significantly during the COVID-19. Krautter et al (2022) found that during the epidemic, the subjective well-being of college students decreased.…”
Section: Introductionmentioning
confidence: 93%
“…However, the study of Baetens et al (2022) shows the pandemic does adversely affect undergraduates' subjective well-being in college. Chen and Ye (2023) found that compared with the period before the epidemic, undergraduates' subjective well-being in college had decreased significantly during the COVID-19. Krautter et al (2022) found that during the epidemic, the subjective well-being of college students decreased.…”
Section: Introductionmentioning
confidence: 93%
“…Experience in university campus green space emphasizes the interaction between university students and campus natural environment. 2 studies tried to classify the interaction by students' activity types in campus green space, for example, physical activity or non-physical activity Holt et al (2019) or mental and social activity (Chen & Ye, 2023). 1 study used the presence of companion to describe the social environment when visiting campus green space .…”
Section: Experience In University Campus Green Space and Mental Healt...mentioning
confidence: 99%
“…Just as mentioned above, 1 study indicated that students who frequently did physical activities in campus green space report more positive mood and less perceived stress than those did non-physical activities (Holt et al, 2019). In contrast, another 2 studies failed to find the association between activity types and mental benefits (Lee et al, 2022;Chen & Ye, 2023). Therefore, evidence for association between types of activity in campus green space and mental health and well-being is limited.…”
Section: Experience In University Campus Green Space and Mental Healt...mentioning
confidence: 99%
“…This trend has inevitably increased environmental concerns. Some of the main culprits highlighted for destroying ecosystems are cable cars and monorails (installed at the expense of forests to facilitate access for hikers) and jet skis, sailboats, mountain bikes, mountain motorcycles, etc., used for water or mountain sports [13].…”
Section: Sports and Environmental Pollutionmentioning
confidence: 99%
“…Thus, sports have the potential to seriously damage the natural environment in many ways. One of the most serious threats is posed by the demand for "nature sports" (including skiing, skin scuba-diving, rock climbing, rafting, yachting, surfing, golf, paragliding, and other sports performed in an undeveloped natural environment), which is likely to increase in the future [12][13][14]. This is because urban areas are becoming increasingly polluted, and people thus increasingly want to return to nature; this desire is supported by economic affluence and leisure time [15,16].…”
Section: Sports and Environmental Pollutionmentioning
confidence: 99%